PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA BEST FRIED CHICKEN (BFC) CABANG SENTOSA SAMARINDA - Mauli Diana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This reseach was conductad at one of the franchise located in Samarinda, which is location on street Sentosa Gg Kembali, namely Best Fried Chicken (BFC). The rose of this study was to examine the effect of product quality, price and brand image of purcasing decisions at Best Fried Chicken (BFC) Sentosa branch Samarinda. And to find out among the variable of produc quality, price and brand image that have a dominant influence on purchasing decisions at Best Fried Chicken (BFC) Sentosa Samarinda Branch. The sampling tachnique used is non probability sampling. The number of sample used was 91 respondent. Data obatained from distribusing questionnaires. The conclusion of this study is that the calculation of this study is that the calculation of the F test variable product quality, price and brand image simultaneously has a significant effect on purchasing decisions as Best Fried Chicken Sentosa Samarinda Branch. while the calculation of the t-test of product quality variables partially does not have a significant effect on purchasing decisions for best fried chicken (BFC) Sentosa Samarinda Branch. In the dominant test, the brand image variable is the most influential variable.